Fungal wood decomposer activities influence community structures of myxomycetes and bryophytes on coarse woody debris. (April 2015) - Fukasawa, Yu; Takahashi, Kazunari; Arikawa, Tomotsugu; Hattori, Tsutomu; Maekawa, Nitaro
Abstract: Dead wood is an important habitat for forest organisms, and wood decay fungi are the principal agents determining the dead wood properties that influence the communities of organisms inhabiting dead wood. In this study, we investigated the effects of wood decomposer fungi on the communities of myxomycetes and bryophytes inhabiting decayed logs. On 196 pine logs, 72 species of fungi, 34 species and seven varieties of myxomycetes, and 16 species of bryophytes were identified. Although white rot was the dominant decay type in sapwood and heartwood, brown and soft rots were also prevalent, particularly in sapwood. Moreover, white rot and soft rot were positively and brown rot negatively correlated with wood pH. Ordination analyses clearly showed a succession of cryptogam species during log decomposition and showed significant correlations of communities with the pH, water content, and decay type of wood. These analyses indicate that fungal wood decomposer activities strongly influence the cryptogam communities on dead wood.